2006
DOI: 10.1002/bdd.529
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of ciclesonide in human nasal epithelial cells

Abstract: Ciclesonide, a corticosteroid in development for allergic rhinitis, is converted to the pharmacologically active metabolite, desisobutyryl-ciclesonide (des-CIC), and des-CIC is subsequently esterified with fatty acids. Various experiments were performed to investigate ciclesonide metabolism in human nasal epithelial cells (HNEC). Human nasal epithelial cells were incubated with (a) 0.1 microM ciclesonide for 1 h and medium without ciclesonide for up to 24 h, (b) esterase inhibitors for 0.5 h followed by 5 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Ciclesonide (CIC) is a novel, nonhalogenated ICS that has been developed to incorporate PK properties that lead to high efficacy and an improved safety profile [ 11 - 15 ]. The prodrug CIC is administered as an inactive parent compound to the lower airways, where it is converted to its pharmacologically active metabolite desisobutyryl-ciclesonide (des-CIC) by endogenous esterases [ 12 , 16 - 19 ] Des-CIC has a high affinity to the glucocorticoid receptor, comparable with beclomethasone-17-monopropionate (BMP), whereas BUD has a slightly lower and FP a higher binding affinity [ 11 ]. Within the lung cells, des-CIC and BUD undergo reversible esterification with fatty acids at the C-21 position of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Ciclesonide (CIC) is a novel, nonhalogenated ICS that has been developed to incorporate PK properties that lead to high efficacy and an improved safety profile [ 11 - 15 ]. The prodrug CIC is administered as an inactive parent compound to the lower airways, where it is converted to its pharmacologically active metabolite desisobutyryl-ciclesonide (des-CIC) by endogenous esterases [ 12 , 16 - 19 ] Des-CIC has a high affinity to the glucocorticoid receptor, comparable with beclomethasone-17-monopropionate (BMP), whereas BUD has a slightly lower and FP a higher binding affinity [ 11 ]. Within the lung cells, des-CIC and BUD undergo reversible esterification with fatty acids at the C-21 position of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that the active metabolite is present for at least 24 hours in nasal epithelia and thus supports once daily administration. 15,16 Ciclesonide, when administered intranasally, shows negligible absorption into systemic circulation. In three separate studies conducted in patients as young as 2 years of age involving administration of ciclesonide nasal spray at doses up to 800 g/day, the majority of serum samples contained undetectable levels of ciclesonide and des-cic.…”
Section: Pharmacology Of Ciclesonidementioning
confidence: 99%
“…24 Preclinical studies conducted in rabbits have indicated that when ciclesonide is delivered as a hypotonic suspension to the nasal mucosa, there is enhanced uptake of ciclesonide, a higher intracellular concentration of the parent and active metabolite, and longer retention of the active metabolite compared with when ciclesonide is suspended and administered in an isotonic medium. 15,16 The intracellular concentrations of ciclesonide and des-cic administered in a hypotonic versus isotonic formulation are displayed in Fig. 3.…”
Section: Formulation Aspects Of Intranasal Ciclesonidementioning
confidence: 99%
“…(Derived from data of Nave et al 2007; Nonaka et al 2007; Sato et al 2007a; Nonaka unpublished data).…”
Section: Figurementioning
confidence: 99%